PERAN SENSE OF BELONGING DALAM MEMBENTUK KESADARAN LINGKUNGAN MASYARAKAT SEKITAR WISATA PANTAI TLANGOH KECAMATAN TANJUNG BUMI KABUPATEN BANGKALAN - Sutra Bukhari, Fiandiras; Rosyidah, Rezkiyah (Jurnal Psikologi Poseidon, 2023)
This study aims to describe the influence of a sense of belonging to the environmental awareness of the community around Tlangoh Beach tourism, Tanjung Bumi District. This study uses a causality quantitative approach. The number of subjects in this study were 100 respondents who are the people around the Tlangoh Beach tourism area, Tanjung Bumi District, which were obtained through a quota sampling technique. The instruments used in this study are the sense of belonging scale based on the theory of Hagerty and Patusky (1995) and the environmental awareness scale based on the theory of Partanen-Hertell et al (1999) and developed by Kokkinen (2013). This study used a simple linear regression test analysis in which the results obtained showed that there was a sense of belonging to the environmental awareness of the community around Tlangoh Beach tourism, Tanjung Bumi District, in the strong category (r = 0.734; p is less than 0.05). Meanwhile, the effective contribution of the sense of belonging variable to environmental awareness is 53.9% while the remaining 46.1% is influenced by other factors.